2015
DOI: 10.1007/s10072-015-2422-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of voice and speech symptoms in early Parkinson’s disease by the Robertson dysarthria profile

Abstract: Changes in voice and speech are thought to involve 75-90% of people with PD, but the impact of PD progression on voice/speech parameters is not well defined. In this study, we assessed voice/speech symptoms in 48 parkinsonian patients staging <3 on the modified Hoehn and Yahr scale and 37 healthy subjects using the Robertson dysarthria profile (a clinical-perceptual method exploring all components potentially involved in speech difficulties), the Voice handicap index (a validated measure of the impact of voice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…As commented in the introduction, statistics show that approximately 75–90% of patients with PD develop dysarthria during the course of the disease [ 4 ][ 9 ][ 7 ][ 8 ]. It means that this is probably the ceiling expected for the sensitivity of a potential system of these characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As commented in the introduction, statistics show that approximately 75–90% of patients with PD develop dysarthria during the course of the disease [ 4 ][ 9 ][ 7 ][ 8 ]. It means that this is probably the ceiling expected for the sensitivity of a potential system of these characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, its use as a ground truth to evaluate the speech is limited, and conclusions have to be extracted having in mind these concerns. Other perceptual scales, specifically developed to evaluate the speech, such as GRBAS, or specifically developed to evaluate dysarthria, such as Roberston Dysarthria Profile (RDP) [ 7 ], or Frenchay Dysarthria Assessment [ 80 ], should be taken into account. A validation procedure in PD patients showed that the RDP has a reasonable reliability, absence of ceiling and floor effects, sufficient internal consistency and scaling assumptions, and considerable correlations with UPDRS-III.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robertson dysarthria profile may be a valuable tool to detect speech/voice disturbances in Parkinson's disease [121]. Indoor and outdoor falls among people with PD often result in activity limitations, participation restrictions, social isolation or premature mortality [122].…”
Section: Parkinson's Diseasementioning
confidence: 99%